OECD-FAO agricultural outlook 2007-2016 (Organisation for Economic Co-operation and Development,Food and Agriculture Organization of the United Nations, 2007)
This is the 13th edition of the Agricultural Outlook and the third time it has been prepared jointly by the Organisation for Economic Cooperation and Development (OECD) and the Food and Agriculture Organisation of the United Nations (FAO). Based on the commodity, policy and country expertise of both organisations, this report forecasts market trends for the world’s main agricultural products for the period 2007 to 2016 and includes an evaluation of recent developments and emerging issues.